Review - Single-Walled Carbon Nanohorn-Based Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (ECS Journal of Solid State Science and Technology, 2017)
Efforts in the broad field of dye-sensitized solar cells (DSSC) are governed by four key challenges: i) the development of photoelectrodes with high charge injection yields and charge collection efficiencies, ii) the development of low-cost buffer layers, which effectively reduce the back reaction of electrons from the transparent conductive oxide (TCO) to the electrolyte, iii) the design of platinum-free counter electrodes (CE), which feature good electrolyte regeneration yields, and iv) the implementation of (quasi) solid-state and iodine-free electrolytes featuring excellent ionic diffusion and conductivity. The introduction of nanocarbons into each component of DSSCs has emerged as a promising strategy to tackle all the aforementioned challenges. Leading examples of nanocarbons are graphene, carbon black (CB), multi-walled carbon nanotubes (MWCNT), and single-walled carbon nanotubes (SWCNT). Here, we focus on single-walled carbon nanohorns (SWCNH), which were successfully integrated into each of the aforementioned parts of DSSCs.
EAM Import::2019-03-13